(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Kilevaya G. А. Establishment and functioning of the Kiev school district during the guardianship EF background Bradtke (1832–1838 years). This article discusses the creation of the initial period of the Kiev school district, when the foundation for future development. The author draws attention to the participation of the college professor’s University of St. Vladimir in the life of the district. Presented the first person trustee EF background Bradtke, thanks znergichnym and determined efforts which occurred the formation Kievekogo scientist District.